FROM LOCAL COMMUNITY TO GLOBAL COMMUNITY: analysis of the phenomenon of growth and influence of virtual catholic communities - López Castellanos, José Roberto (Abierta. Anuario de investigación, 2015)
In order to understand the phenomenon of growth and influence being exerted by virtual catholic communities, it became necessary to analyze the needs and behaviors of the audience. Hence, it was discovered that the females hold within these communities the greater level of participation and representation. Tolerance to criticism allows achieving the goal of generating conversation amongst users. The main factor that has motivated growth within these types of communities is the figure of Pope Francis, followed by alliances, constant activity and the projection of a content which is aesthetically pleasing. Finally, it was discovered that the greater the scope, the greater the probability of generating some type of influence on beliefs, purposes and/or actions. ECMH ABIERTA_AT_N9-2015-59-67.